The horizons of rural touring: re-imagining the rural tour - Branson, Mathilda (2017)
The subject of this thesis is the UK rural touring theatre sector, and the possibility of formal innovation for rural touring. My research has been funded by the Arts and Humanities Research Council as part of their Collaborative Doctoral Awards scheme, and has come about as a result of a partnership between The University of Nottingham and New Perspectives Theatre Company, which has enabled a combination of theoretical and practice-based research. In the rural touring sector, companies like New Perspectives tour productions to village halls and other community venues, where work is programmed by volunteer promoters. This area of the UK theatre ecology is thriving, but overlooked in academic studies of theatre. I argue that rural touring is distinct from theatre taking place in non-rural contexts in its audiences, places of performance and distribution model. Audience members tend to know each other, and their reasons for attendance often include a wish to socialise with fellow members of their community instead of, or as well as, a desire for a particular artistic experience. Rural touring venues are usually multi-purpose community spaces, used for exercise classes and social groups alongside their use as performance venues. Staff at regional touring schemes act as intermediaries in the distribution model, brokering the booking process between companies and promoters, whose programming choices may be governed by their role as members of the audience community. This thesis expands on scholarship related to theatre audiences and places of performance by highlighting these differences and their implications.